Climate‐change impact considerations for freshwater‐fish conservation, with special reference to the aquarium and zoo community. Issue 1 (12th March 2013) - Pearce‐Kelly, P.; Khela, S.; Ferri, C.; Field, D.
Abstract : Freshwater systems are already in a worse condition overall than any other broad ecosystem type and have long suffered from a lack of adequate conservation attention. Likewise, relatively little attention is given to the climate‐change impact vulnerability and response requirements of these systems. However, it is clear that freshwater habitats and their rich biodiversity are acutely vulnerable to a wide range of direct and indirect climate‐change impacts. In addition to the severe socio‐economic implications, these impact and response issues present an urgent engagement challenge for the conservation community. Although species‐level conservation options are limited in the context of the overall biodiversity threat, it is evident that even under the most optimistic of climate‐change impact scenarios many more species will require ex situ management for their survival. This conservation challenge will be compounded by a growing number of species for which there is no realistic likelihood of eventual persistence in the natural state. These issues highlight an urgent need for realistic climate‐change impact considerations to be factored into threat evaluations, conservation planning and public‐engagement initiatives.